PENGARUH LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS MODEL PEMBELAJARAN TERPADU TIPE SEQUENCED TERHADAP KOMPETENSI SISWA PADA MATA PELAJARAN IPA KELAS VIII DI SMP NEGERI 3 PARIAMAN - Yogi Prima Candra; Djusmaini Djamas; Gusnedi Gusnedi (PILLAR OF PHYSICS EDUCATION, 2016)
Sciences achievement competence of learners who not yet  maximum of one due to lack of use of teaching materials. The curriculum requires that the material be delivered in an integrated manner. Learning sciences delivered in an integrated manner can be supported by the implementation of integrated learning model. One type of integrated learning model is a sequenced type (sequence). Integrated learning model allows educators deliver sequenced type of learning in an integrated and sequenced. Educators can reorder re-learning materials that are interrelated so that students obtain holistic and meaningful learning. Research goal is to investigate the influence of student worksheet based integrated learning  model of the type squenced  on the achievement natural sciences competence of learners second grade class in pariaman 3 junior high school. This research is a Quasi Experiment with the design of Randomized Control Group Only Design. The population in this reseacrh was the students of second grade class in pariaman 3 junior high school. Sample was taken by cluster random sampling. Competence of learners divided into competence attitudes, knowledge and skills. Attitude competency assessment instrument using observation sheets, instrument competency knowledge using written tests and instrument competency skills in using performance assessment rubric. Statistical analysis was performed on the data to the stages of normality test, homogeneity and hypothesis testing. The average value of competence attitudes, knowledge and skills of students in the experimental class respectively, are 81.98, 47.07 and 77.15. The average value of competence attitudes, knowledge and skills on successively control class is 84.34, 42.24, and 73.49. Data analysis was conducted on these data using the equality test two averages. Analysis of the data yielded the t value for each competency, that is 1,04, 2,304, and 1,709. From value of t only in the aspect of knowledge that is outside H0. This means the only aspect of the student's knowledge of the worksheets have a significant impact. Observations have shown that the use student worksheet based of integrated learning model sequenced types increased the motivation of learners